Self‐determination theory as a foundation for personality researchers. Issue 1 (23rd January 2019) - Sheldon, Kennon M.; Prentice, Mike
Abstract: In this introductory article, we first describe the impetus for this special issue. What made us think that self‐determination theory (SDT) might provide a sort of foundation for the rest of personality psychology? For readers unfamiliar with SDT, we then provide a historical overview that covers the evolution of the six "mini‐theories" that currently compose SDT: cognitive evaluation theory, causality orientations theory, organismic integration theory, basic psychological needs theory, goal contents theory, and relational motivation theory. Following each section are preliminary suggestions about how each mini‐theory might be useful or informative in other branches of personality. This special issue contains nine articles, each of which makes its own attempt to newly link its area of personality research to SDT. Even if SDT is not the appropriate seed for greater consilience in personality psychology, we urge the field not to neglect the search for unifying principles (Sheldon, Cheng, & Hilpert, 2011); it may finally be time to renew the search for a "grand theory" in personality.